Analysis of E-Ticketing Service Information System Application using COBIT 5 Framework - Mamang Weking, Philipus Novenando; Wira Partha, I Gusti Ngurah; Alit Swamardika, Ida Bagus (International Journal of Engineering and Emerging Technology, 2019)
The need for goods is a major commodity for individuals, groups and agencies. Goods services are one of the main factors in managing user needs regarding goods repairs for a longer use. PT. Z Bali is a part company of PT. W Bali Group is specialized in goods service. Service delivery of goods has been assisted by an information system in the form of an application called E-Ticketing Service. The importance of using applications in services needs to be reviewed for evaluating the use of the E-Ticketing Service application information system. in this study, the standard use for performance evaluation process that is COBIT 5 framework where the chosen domain is the DSS domain (Delivery, Service, and Support). COBIT 5 can help in determining the needed requirement in the audit process. Based on the evaluation of the use of the E-Ticketing Service application, the capabilities obtained are Level 2 Managed. To improve the value of capabilities can be done by giving advice in the form of recommendations to increase the usability of E-Ticketing Service application services.